Safety and efficacy of anti-il6-receptor tocilizumab use in severe and critical patients affected by coronavirus disease 2019: A comparative analysis. Issue 4 (October 2020) - Rossotti, Roberto; Travi, Giovanna; Ughi, Nicola; Corradin, Matteo; Baiguera, Chiara; Fumagalli, Roberto; Bottiroli, Maurizio; Mondino, Michele; Merli, Marco; Bellone, Andrea; Basile, Andriano; Ruggeri, Ruggero; et al.
Highlights: Cytokine release syndrome seems to play a pivotal role in COVID-19 pathogenesis. Tocilizumab is one of the most promising drugs for COVID-19. Tocilizumab halved the mortality in critical patients compared to standard of care. A transient respiratory function worsening is observed soon after administration. Severe infective complications are more common than in rheumatologic setting. Abstract: Background: As the novel SARS-CoV-2 pandemic occurred, no specific treatment was yet available. Inflammatory response secondary to viral infection might be the driver of severe diseases. We report the safety and efficacy (in terms of overall survival and hospital discharge) of the anti-IL6 tocilizumab (TCZ) in subjects with COVID-19. Methods: This retrospective, single-center analysis included all the patients consecutively admitted to our Hospital with severe or critical COVID-19 who started TCZ treatment from March 13th to April 03rd, 2020. A 1:2 matching to patients not treated with TCZ was performed according to age, sex, severity of disease, P/F, Charlson Comorbidity Index and length of time between symptoms onset and hospital admittance. Descriptive statistics and non-parametric tests to compare the groups were applied. Kaplan Meier probability curves and Cox regression models for survival, hospital discharge and orotracheal intubation were used. Results: Seventy-four patients treated with TCZ were matched with 148 matched controls. They were mainly males (81.5%), Caucasian (82.0%) and with a median age of 59 years. The majority (69.8%) showed critical stage COVID-19 disease. TCZ use was associated with a better overall survival (HR 0.499 [95% CI 0.262–0.952], p  = 0.035) compared to controls but with a longer hospital stay (HR 1.658 [95% CI 1.088–2.524], p  = 0.019) mainly due to biochemical, respiratory and infectious adverse events. Discussion: TCZ use resulted potentially effective on COVID-19 in terms of overall survival. Caution is warranted given the potential occurrence of adverse events. Financial support: Some of the tocilizumab doses used in the subjects included in this analysis were provided by the "Multicenter study on the efficacy and tolerability of tocilizumab in the treatment of patients with COVID-19 pneumonia" (EudraCT Number: 2020-001110-38) supported by the Italian National Agency for Drugs (AIFA). No specific funding support was planned for study design, data collection and analysis and manuscript writing of this paper.